Preparation and Performance Testing of Steel Slag Concrete from Steel Solid Waste - Bao Yuan; Dongnan Zhao; Jialiu Lei; Shengqiang Song (Buildings, 2024)
In this paper, steel slag powder was used to replace part of the cement in road concrete, and group tests were carried out on coarse aggregates with different water–cement (W/C) ratios, different steel slag parameters, and different particle sizes. A sample of 100 mm × 100 mm × 100 mm was prepared and cured for 3 days, 7 days, and 28 days. In addition, the fluidity and compressive properties of the samples were also tested. The outcomes of this study revealed that, at a constant W/C ratio, increasing the proportion of steel slag improved the concrete’s fluidity but reduced its compressive strength; the 3-day (3 d) compressive strength of 40% steel slag was lower because the early activity of steel slag was lower than that of cement; steel slag also decreased the early-hydration rate of concrete. Comparisons across different W/C ratios demonstrated that steel slag made a more significant contribution to lower W/C ratios than higher ones. The water requirement for steel slag was relatively moderate, and the compressive strength of steel slag concrete with a high W/C ratio notably improved in the later stages. Based on the experimental conditions, the optimal content of steel slag was found to be 35%. Reusing steel slag as a replacement for sand in coarse aggregate can effectively lower costs and offer an innovative approach to steel slag treatment.